The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4cp01187b
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced structural rearrangement of the Fe(ii) coordination geometry in metallo-supramolecular polyelectrolytes

Abstract: Rigid rod-type metallo-supramolecular coordination polyelectrolytes with Fe(II) centres (Fe-MEPEs) are produced via the self-assembly of the ditopic ligand 1,4-bis(2,2':6',2''-terpyridine-4'-yl)benzene (tpy-ph-tpy) and Fe(II) acetate. Fe-MEPEs exhibit remarkable electrochromic properties; they change colour from blue to transparent when an electric potential is applied. This electrochemical process is generally reversible. The blue colour in the ground state is a result of a metal-to-ligand charge transfer at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This means that in fact the Fe complex in Fe-MEPE does not undergo a noticeable structural change during charging and discharging. From a previous XAFS study of these materials [27] we know that the iron ion is coordinated in a pseudo-octahedral environment with the nitrogen atoms of the pyridine rings in the vertices. The axial Fe-N distance is 1.95 Å, and the equatorial Fe-N distance amounts to 1.98 Å.…”
Section: Optical Electrochemical and Spectro-electrochemical Propertmentioning
confidence: 98%
“…This means that in fact the Fe complex in Fe-MEPE does not undergo a noticeable structural change during charging and discharging. From a previous XAFS study of these materials [27] we know that the iron ion is coordinated in a pseudo-octahedral environment with the nitrogen atoms of the pyridine rings in the vertices. The axial Fe-N distance is 1.95 Å, and the equatorial Fe-N distance amounts to 1.98 Å.…”
Section: Optical Electrochemical and Spectro-electrochemical Propertmentioning
confidence: 98%
“…1,4-Di([2,2 0 :6 0 ,2 00 -terpyridin]-4 0 -yl)benzene has been used as a ligand in the formation of mononuclear complexes (Santoni et al, 2013;Laramé e-Milette & Hanan, 2017), binuclear complexes (Santoni et al, 2013;Schmittel et al,2006;Maekawa et al, 2004), tetranuclear complexes (Schmittel et al, 2005), one-dimensional coordination polymers (Koo et al, 2003), two-dimensional coordination polymers (Bulut et al, 2015;Jones et al (2010), and numerous metallo-supramolecular polymers (without reported crystal structures), see for example: Vaduvescu & Potvin, 2004;Nishimori et al, 2007;Han et al, 2008;Schwarz et al, 2010;Ding et al, 2012;Muronoi et al, 2013;Szczerba et al, 2014;Munzert et al, 2016;Meded et al, 2017;Bera et al, 2018. A search of the Cambridge Structural Database (CSD, Version 5.40, update August 2019; Groom et al, 2016) for the ISSN 2056-9890 title compound yielded only nine hits (see supporting information), which included the report on the structure of the orthorhombic polymorph, Form II, by Fernandes et al (2010).…”
Section: Chemical Contextmentioning
confidence: 99%
“…In the ongoing drive toward new functional supramolecular systems, a constant need exists for the discovery and development of new ligand systems, binding motifs, and molecular scaffolds, in order to diversify the existing chemical toolbox and rationally pursue specific applications. To this end, significant progress has been made recently in establishing modular ligand sets for further development into supramolecular systems. , Doing so requires a thorough basis in the fundamental coordination chemistry and structural trends of archetypal systems, to establish the necessary understanding of the subtle geometric and electronic effects which are well-known to strongly influence the bulk properties of such systems. The polypyridine family of ligands are well-known metallosupramolecular ligand scaffolds, widely exploited in transition metal coordination chemistry, due to the predictable coordination behavior and favorable electronic and magnetic properties of bipyridine and terpyridine d-metal ion complexes. , These structures have found myriad applications, including as dye-sensitized solar cells, redox photocatalysts, molecular electronics, and spin crossover devices. As well-established starting points, functional 2,2′-bipyridine derivatives are ideally suited for the installation of new substitution patterns and functional groups . Although direct derivatization of the deactivated pyridine ring itself can be synthetically cumbersome compared to other nitrogen heterocycles, new synthetic methods are continually emerging for the synthesis of functional bipyridine ligands. , …”
Section: Introductionmentioning
confidence: 99%